2009
DOI: 10.1021/jp9074064
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Investigations on Oxidative Stability of Solvents and Oxidative Decomposition Mechanism of Ethylene Carbonate for Lithium Ion Battery Use

Abstract: The electrochemical oxidative stability of solvent molecules used for lithium ion battery, ethylene carbonate (EC), propylene carbonate, dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate in the forms of simple molecule and coordination with anion PF(6)(-), is compared by using density functional theory at the level of B3LYP/6-311++G (d, p) in gas phase. EC is found to be the most stable against oxidation in its simple molecule. However, due to its highest dielectric constant among all the solve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
206
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(229 citation statements)
references
References 27 publications
14
206
1
Order By: Relevance
“…It is possible that the CO 2 is mainly caused by the oxidation of EC. [11][12][13] The bottom panels show that carbonyl sulfide is produced in the cells containing PES charged to 4.7 V. This is consistent with oxidation of PES at the positive electrode, creating the fragment carbonyl sulfide, which is similar to CO 2 from the oxidation of EC. The bottom left panel also shows that methyl formate might be produced during this second gas step.…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…It is possible that the CO 2 is mainly caused by the oxidation of EC. [11][12][13] The bottom panels show that carbonyl sulfide is produced in the cells containing PES charged to 4.7 V. This is consistent with oxidation of PES at the positive electrode, creating the fragment carbonyl sulfide, which is similar to CO 2 from the oxidation of EC. The bottom left panel also shows that methyl formate might be produced during this second gas step.…”
Section: Resultssupporting
confidence: 52%
“…It has been argued, both experimentally and through computational work, that EC can be oxidized to produce mainly carbon dioxide (CO 2 ) and carbon monoxide (CO) in much smaller quantities. [11][12][13] Gas consumption has, to the authors' knowledge, however not been the subject of much scholarship, but, as will be shown, occurs and is important. There nonetheless have been suggestions that gases could polymerize on the surface of electrodes, e.g.…”
mentioning
confidence: 98%
“…• C. For instance, the EC solvent may undergo the oxidative decomposition resulting in radical cation (EC •+ ), 24 as depicted in Fig. 9.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, Zhang et al 34 presented ab-initio calculations, which proposed a thermodynamically favorable pathway for CO 2 evolution upon the anodic oxidation of EC. In a later, more detailed ab-initio computational study, Xing et al 32 evaluated several feasible pathways for CO 2 and CO evolu- 34 do not report on a pathway leading to CO formation, Xing et al 32 propose another, compared to CO 2 formation (i.e., path 1) energetically less favorable pathway, which can lead to CO release via the formation of formaldehyde and +• O=CH 2 (see path 3 in Scheme 1). 32 Unfortunately, since the 12 CO 2 / 12 CO ratio in our experiments is determined by the anodic oxidation of both EC and conductive carbon (Super C65), the data in Table II and in Figure 4 does not allow to quantify the CO 2 /CO ratio exclusively due to the anodic oxidation of EC.…”
Section: Discussionmentioning
confidence: 99%